PENGARUH KOMPETENSI DAN SISTEM TEKNOLOGI INFORMASI TERHADAP KUALITAS PELAPORAN BARANG MILIK DAERAH KABUPATEN PARIGI MOUTONG - Yasir, Moh. (Katalogis, 2018)
The purpose of this study is determine and analyze simultaneous and partial influence of competency and information Technology Systems on the quality of local assets report. reporting Regional Property (BMD) either simultaneously or partially. Respondents consist of 41 officials in charge in local assets administration of Parigi Moutong, who selected with random sampling. Method of analysis in is multiple linear regression. The results shows that Competency and Information Technology System simultaneously and partially have positive and significant influence on the quality of local assets report of Parigi Moutong. Coefficient determination shows Adjusted R-Square of 0.311 or 31.1%. This means that Â 31.1 of the quality of report influence of competency and information Technology Systems, whole 68.9% influenced by other variables that are not studied.